ConsRM: collection and large-scale prediction of the evolutionarily conserved RNA methylation sites, with implications for the functional epitranscriptome. Issue 6 (17th May 2021) - Song, Bowen; Chen, Kunqi; Tang, Yujiao; Wei, Zhen; Su, Jionglong; de Magalhães, João Pedro; Rigden, Daniel J; Meng, Jia
Abstract: Motivation N6-methyladenosine (m 6 A) is the most prevalent RNA modification on mRNAs and lncRNAs. Evidence increasingly demonstrates its crucial importance in essential molecular mechanisms and various diseases. With recent advances in sequencing techniques, tens of thousands of m 6 A sites are identified in a typical high-throughput experiment, posing a key challenge to distinguish the functional m 6 A sites from the remaining 'passenger' (or 'silent') sites. Results: We performed a comparative conservation analysis of the human and mouse m 6 A epitranscriptomes at single site resolution. A novel scoring framework, ConsRM, was devised to quantitatively measure the degree of conservation of individual m 6 A sites. ConsRM integrates multiple information sources and a positive-unlabeled learning framework, which integrated genomic and sequence features to trace subtle hints of epitranscriptome layer conservation. With a series validation experiments in mouse, fly and zebrafish, we showed that ConsRM outperformed well-adopted conservation scores (phastCons and phyloP) in distinguishing the conserved and unconserved m 6 A sites. Additionally, the m 6 A sites with a higher ConsRM score are more likely to be functionally important. An online database was developed containing the conservation metrics of 177 998 distinct human m 6 A sites to support conservation analysis and functional prioritization of individual m 6 A sites. And it is freely accessible at: https://www.xjtlu.edu.cn/biologicalsciences/con .